Genotype-specific cortisol production associated with Cushing's syndrome adenoma with PRKACA mutations. (1st December 2021) - Baba, Ryuta; Oki, Kenji; Gomez-Sanchez, Celso E.; Otagaki, Yu; Itcho, Kiyotaka; Kobuke, Kazuhiro; Kodama, Takaya; Nagano, Gaku; Ohno, Haruya; Yoneda, Masayasu; Hattori, Noboru
Abstract: The intracellular molecular mechanisms underlying the genotype of cortisol-producing adenoma (CPA) have not been fully determined. We analyzed gene expressions in CPA and the human adrenocortical cell line (HAC15 cells) with PRKACA mutation. Clustering analysis using a gene set associated with responses to cAMP revealed the possible differences between PRKACA mutant CPAs and GNAS and CTNNB1 mutant CPAs. The levels of STAR, CYP11A1, CYP17A1, CYP21A2, and FDX1 transcripts and cortisol levels per unit area in PRKACA mutant CPAs were significantly higher than those in GNAS mutant CPAs. PRKACA mutations led to an increase in steroidogenic enzyme expression and cortisol production in HAC15 cells. Transcriptome analysis revealed differences between PRKACA mutant CPAs and GNAS and CTNNB1 mutant CPAs. Cortisol production in PRKACA mutant CPAs is increased by the cAMP-PKA signaling pathway-mediated upregulation of steroidogenic enzymes transcription. The intracellular molecular mechanisms underlying these processes would be notably important in PRKACA mutant CPAs. Highlights: RNA sequencing analyses showed that PRKACA mutants were separated with others. Cushing's adenoma with PRKACA mutant had elevated steroidogenic enzyme expression. Cortisol levels per unit area were high in Cushing's adenoma with PRKACA mutant. PRKACA mutation increased in steroidogenic enzyme expression in HAC15 cells. PRKACA mutations led to an increase in cortisol production in HAC15 cells.